FDG PET/CT Imaging of Calcified Sister Mary Joseph Nodule - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2016)
Sister Mary Joseph nodule (SMJN) refers to any metastatic deposit in the periumbilical region. Herein, we report a very rare case of calcified SMJN from ovarian papillary serous adenocarcinoma showing intense FDG uptake.
Keywords: FDG; PET/CT; calcified Sister Mary Joseph nodule; UMBILICAL METASTASIS; OVARIAN-CARCINOMA